Preventive Efforts On Criminal Violence Of Women - Mohamad Sugiyarto; Umar Ma'ruf (Universitas Islam Sultan Agung, 2020)
The objectives of this study were (1) to find out and analyze why there was a criminal act of violence against women in Pati Regency, (2) To identify and analyze efforts to overcome criminal acts of violence against women in Pati Regency, (3) To identify and analyze the obstacles what are the obstacles) in law enforcement for criminal acts of violence against women in Pati District and what are the solutions. The method used in this research is empirical juridical research. Sources and data types use primary data and secondary data. The data collection process was carried out by observing techniques, interviews, documentation, and literature, while the analysis method used was qualitative analysis. The research problem is analyzed by using Human Rights Theory and Law Enforcement Theory.In the effort to overcome and prevent perpetrators of domestic violence, it must be supported by increasing legal awareness of the community. Public legal awareness is a part of legal culture. This is said to be one part, because so far there is a perception that the legal culture only includes the legal awareness of the community. In essence, there are several approaches that can be taken to deal with domestic violence, namely through a preventive approach, a curative approach and a medical approach.